Analisis Psikologis Terhadap Adopsi Anak Perspktif Konseling Hukum Keluarga Islam : Analisis Psikologis Terhadap Adopsi Anak Perspktif Konseling Hukum Keluarga Islam - Nakma Ussolikhah; Dindin Syarief Nurwahyudin (Program Studi Hukum Keluarga (Ahwal Syakhshiyah), 2026)
The threats to education in the 21st century are increasingly complex and growing rapidly. Several threats that need to be paid attention to justice and a decline in the self-existence of children in the category of adopted children, this is influenced by low self concept in children, which affects the development of personal and academic character. Children's character is the initial foundation of the education system. The aim of this research is to instill character in adopted children by building self-confidence and protection under Islamic law. Research method with a normative juridical approach, descriptive qualitative conceptual approach, library study design with data collection techniques analyzing e-journals and e-books. The research results describe that family counseling is an integral part of helping adopted children overcome problems in the personal and social spheres to obtain justice as biological children. The function of education in schools is one of the elements of success for children when children are able to develop their inner potential optimally. Based on the results of the analytical study, it is known that children can have positive personalities and develop according to developmental tasks, including achieving the child's development of religious knowledge and behavior. The protection rights of adopted children have the same level as biological children. This is believed to be an effort to uphold justice in parenting within the family.